2019
DOI: 10.1371/journal.pone.0218137
|View full text |Cite
|
Sign up to set email alerts
|

Trust but verify: Is there a role for active surveillance in monitoring adverse events in Zimbabwe’s large-scale male circumcision program?

Abstract: Introduction Ensuring quality service provision is fundamental to ZAZIC’s voluntary medical male circumcision (MC) program in Zimbabwe. From October, 2014 to September, 2017, ZAZIC conducted 205,847 MCs. Passive surveillance recorded a combined moderate and severe adverse event (AE) rate of 0.3%; reported adherence to follow-up was 95%, suggesting program safety. Despite encouraging passive surveillance data, verification of data quality and accuracy would increase confidence in AE identification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…MC is safe and major complications are rare; thus, most follow-up visits are unnecessary [26,27]. Adverse events (AEs) from gold-standard active surveillance [25,28,29] report 5-7% AEs [4,[30][31][32] while routine passive surveillance reports below the commonly-accepted 2% AE rate [33][34][35][36][37]. To ensure client safety, current global standards for high quality MC services nevertheless require at least one follow-up within 14 days [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…MC is safe and major complications are rare; thus, most follow-up visits are unnecessary [26,27]. Adverse events (AEs) from gold-standard active surveillance [25,28,29] report 5-7% AEs [4,[30][31][32] while routine passive surveillance reports below the commonly-accepted 2% AE rate [33][34][35][36][37]. To ensure client safety, current global standards for high quality MC services nevertheless require at least one follow-up within 14 days [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…First, despite low AE rates in the ZAZIC program that suggest overall patient safety [ 27 29 ], our results indicate that the drive for target achievement leaves quality gaps throughout the cascade of VMMC service delivery. Most KIs noted weaknesses in counseling sessions: both pre-and post-operative counseling may be shortened or group and individual sessions may be combined.…”
Section: Discussionmentioning
confidence: 87%
“…Reported adherence to follow-up visits, another indicator of program quality [21], was good with routine data indicating 90% of men attending at least one review visit within 14 days of procedure. However, ZAZIC investigation focused on active surveillance of AEs and found higher AE rates (~4%; range 1-8%) and, as part of the study, observed lower follow-up than reported [22]. As ZAZIC strives to achieve high VMMC productivity targets, early signs of weakness in quality service delivery require immediate action to maintain its dedication to both patient safety and program performance.…”
Section: Plos Onementioning
confidence: 79%
See 2 more Smart Citations